Flipped Learning As A New Educational Paradigm: An Analytical Critical Study - Ahmed, Hanaa Ouda Khadri (European Scientific Journal, ESJ, 2016)
A literature on the flipped learning model has been reviewed. Therefore, the new form of education is worthy enough to be further studied. It is believed that flipped learning has gained great attention of many researchers as a result of what educators are implementing at their classrooms. The main objective of the paper is proposing an educational analytical critical framework for flipped learning that has powerful effects for who are concerned with educational development. The broad groundwork of literature on the flipped learning, described as the inverted learning, provided a foundation for the present study. This groundwork of literature used the term flipped learning and examined its effects on the pedagogy in education. The educational analytical critical framework of flipped learning developed in this paper includes components that reveals different views of flipped learning from just a â€œfashionâ€ of adding more mechanism to the classroom to it is as a tool for shifting present pedagogy customized according to the individual needs of the learners instead of the whole group. The components of the framework are: instructional foundations, learning theories, Bloomâ€™s taxonomy, and conceptual framework of the flipped education that is discussed in the light of its connection to the educational foundations of flipped learning. Research method used was descriptive method and method of philosophical analysis.